ANALISIS PERMASALAHAN KESEHATAN PADA NARAPIDANA DILEMBAGA PEMASYARAKATAN - Afif Adnan Zuhair (JURNAL KESEHATAN INDRA HUSADA, 2020)
In accordance with what we see today, the population in prison is increasing and the health problems of prisoners are quite large. The correctional facility is currently designed taking into account the sentence of the detainee. The purpose of this study is to analyze the health of a prisoner in prison, because health indicates a major problem in supervision of correctional institutions related to mental health, as well as infectious diseases. Effective delivery of health services to detainees depends on a partner or a prison warden and one way to overcome this is by the existence of new regulations that must be considered by the government so that the health of prisoners can be maintained.